Design of a Pharmacy Curriculum on Patient Centered Communication Skills - Majanne Wolters; Jacqueline G. van Paassen; Lenneke Minjon; Mirjam Hempenius; Marie-Rose Blokzijl; Lyda Blom (MDPI AG, 2021)
For delivering high quality pharmaceutical care pharmacy students need to develop the competences for patient centered communication. The aim of the article is to describe how a curriculum on patient centered communication can be designed for a pharmacy program. General educational principles for curriculum design are based on the theories of constructive alignment, self-directed learning and the self-determination theory. Other principles are paying systematic and explicit attention to skills development, learning skills in the context of the pharmacy practice and using a well-balanced system for the assessment of students' performance. Effective educational methods for teaching communication skills are small group training sessions preferably with (simulation) patients, preceded by lectures or e-learning modules. For (formative or summative) assessment different methods can be used. The Objective Structured Clinical Exam (OSCE) is preferred for summative assessment of communication competence. The principles and educational methods are illustrated with examples from the curriculum of the master Pharmacy program of Utrecht University (The Netherlands). The topics 'pharmaceutical consultations on prescription medicine,' 'pharmaceutical consultations on self-care medication' and 'clinical medication reviews' are described in detail. Finally, lessons learned are shared.